Investigating the source of Planck-Detected AME: High-resolution observations at 15 GHz - Perrott, Y.; Scaife, A.; Hurley-Walker, Natasha; Grainge, K. (Hindawi Publishing Corporation, 2013)
The Planck 28.5 GHz maps were searched for potential Anomalous Microwave Emission (AME) regions on the scale of ~3° or smaller, and several new regions of interest were selected. Ancillary data at both lower and higher frequencies were used to construct spectral energy distributions (SEDs), which seem to confirm an excess consistent with spinning dust models. Here we present higher resolution observations of two of these new regions with the Arcminute Microkelvin Imager Small Array (AMI SA) between 14 and 18 GHz to test for the presence of a compact (~10 arcmin or smaller) component. For AME-G107.1+5.2, dominated by the Hii region S140, we find evidence for the characteristic rising spectrum associated with either the spinning dust mechanism for AME or an ultra- /hypercompact Hii region across the AMI frequency band; however, for AME-G173.6+208 we find no evidence for AME on scales of ~2–10 arcmin.